Characteristics of rice husk tar secondary thermal cracking. (15th December 2015) - Zhai, Ming; Wang, Xinyu; Zhang, Yu; Dong, Peng; Qi, Guoli; Huang, Yudong
Abstract: A two-stage fixed bed pyrolysis system for rice husk tar high-temperature thermal cracking was designed. Pyrolysis of rice husk and high-temperature thermal cracking of the rice husk tar were separated. High-temperature flue gas was used to promote rice husk pyrolysis, and then high-temperature secondary thermal cracking tar started in the high-temperature environment. The characteristics of secondary thermal cracking of rice husk tar were investigated. Results show that rice husk tar yield is 18 mg/kg of dry rice husk, or 11.7 mg/Nm 3 at 1200 °C, and no tar is collected at 1300 °C. At the temperature of 1200 °C and residence time of 0.5 s, the rate of decline of tar reaches the maximum. The oxy-organics content in the tar at 700 °C reaches the maximum 24.5% and becomes zero at 1100 °C. The naphthalene content in the tar reaches the maximum 26.4% at 800 °C. With the increase in temperature, all the tar converts into non-condensable gas and char finally. Highlights: A two-stage fixed bed for rice husk tar secondary thermal cracking was designed. Tar yield is 11.7 mg/Nm 3 at 1200 °C, and no tar is collected above 1300 °C. Naphthalene in the tar reaches the maximum at 800 °C. With temperature rise, tar converts from PAHs to non-condensable gas and char. Tar is cracked completely at high temperature with short residence time.